Comparison ofArbitrarily Primed PCR, Antibiotic Resistance and Plasmid Profiling for Differentiating Salmonella enteritidis Isolated from Fish - Radu, S.; Sahilah, A. M.; Rusul, G.; Samuel, L.; Zuraini, M. I.; Nasreldin, E.H. (Asian Fisheries Society, 2000)
A total of 28 isolates of Salmonella enteritidis isolated from Tilapia (Tilapia mossambica) were investigated through arbitrarily primed polymerase chain reaction (AP-PCR) fingerprinting using three primers, plasmid profiling and their antibiotic resistance patterns. All 28 isolates carried at least one plasmid ranging in size from 1.4 to 38 megadalton that enabled the S. enteritidis to be grouped into nine plasmid profiles. Isolates were resistant to nalidixic acid (21.1%), penicillin (39.3%) and streptomycin (71.4%), and were susceptible to carbenicillin, cephalothin,kanamycin, rifampicin and tetracycline. Seventeen isolates (60.7%) were resistant to a single antibiotic and eleven (39.3%) were resistant to two antibiotics; thus separating the isolates into six antibiotic resistance patterns. The AP-PCR results showed that the collection of isolates were genetically very heterogenous. AP-PCR enabled us to differentiate the isolates into 28 AP-PCR types. Analysis derived from these data in combination (AP-PCR, plasmid profiling and antibiotic resistance patterns) showed that all 28 isolates were distinct and were grouped into 28 individual groups. Our results demonstrate that AP-PCR fingerprinting method is more sensitive than plasmid profiling and antibiotic resistance patterns with respect to the individualization of the isolates used in this study.